Season of the sandstorms - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series. Merlin missions, 2017)
Guided by a magic rhyme, Jack and Annie travel to ancient Baghdad on a mission to help the Caliph disseminate wisdom to the world.